ANALYSIS OF SERVICE QUALITY FACTORS TOWARDS MSME INTEREST ON MUDHARABAH FINANCING PRODUCT IN BSI BEKASI CITY - Kaban, Reny Fitriana; Kuswanto, Ammanda Rissa (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to analyze the influence of service quality factors that affect the interest of MSMEs using mudharabah financing at Bank Syariah Indonesia Bekasi City. This study uses a survey method in the form of primary data by distributing questionnaires to customers who have micro, small, and medium businesses that use mudharabah financing at Bank Syariah Indonesian Bekasi City and the testing of this research uses descriptive analysis tests, validity, and reliability tests, while for the analysis tool using analytical tests. Multiple linear and hypothesis testing using t-test and f-test. The results of this study indicate that together the service quality variables with indicators (compliance, tangibleness, reliability, responsiveness, confidence, and empathy) have a positive and significant effect on the interest of MSME while the variable that most influences the interest of MSME is the service quality variable with empathy indicators.